Chili disease system (CDS) - Nur Syahkina, Sahabe Marubi (2012)
Chili disease system is a web-based expert system that is developed to help staff of Jabatan Pertanian Jubli Perak identify and diagnose the disease of chili.With the useful information provided that is symptoms,and the pesticide to help prevent the diseases.Chili Disease System(CDS)help user to get the information about the disease that may attack the chili,and the symptoms.There are various types of disease of this crop that affected the product of chili.Naturally,the disease may cause by the insect pests,or maybe other symptoms.So,the changes that happened at the fruits,stem,or leaf can recognize the diseases.Current system to identify the problem was actually by doing observations regularly. The data uses are based on written document and logical thinking,but the data will probably lose if the documents are not sorted properly.By using forward chaining, the system implements a rule-based expert system technique to match and fired the fact with user input to get information about the disease of chili.This system applied rapid application development methodology for the system development process.Other than that,this application can imitate human thought and making decision almost accurate like the expert.